Academic Self-Efficacy of Upper Grade Students: The Impact of Tutoring: Efikasi Diri Akademik Siswa Kelas Atas: Dampak Bimbingan Belajar - Alifiandi, Muhammad Nufal; Ansyah, Eko Hardi (Indonesian Journal of Education Methods Development, 2023)
This quantitative comparative study aims to examine the differences in academic self-efficacy among upper grade students in elementary schools in Sidoarjo, specifically in relation to tutoring. The research population consisted of fourth and fifth-grade students from Larangan State Elementary School and Muhammadiyah 2 Kedungbanteng Elementary School, with a total of 185 subjects. The Academic Self-Efficacy Scale, comprising 27 items, was used to measure self-perceived abilities. Data analysis involved the two independent sample t-test technique. The results indicated no significant difference (p > 0.5) in academic self-efficacy between students who received tutoring and those who did not. The Cronbach's Alpha test demonstrated high reliability (0.890) for the academic self-efficacy scale. This study highlights that tutoring did not have a significant impact on the academic self-efficacy of upper grade students. These findings provide implications for educators and parents in considering alternative strategies to enhance students' academic self-efficacy beyond traditional tutoring approaches. Highlight: No significant difference: The study reveals that there is no significant difference in academic self-efficacy between students who receive tutoring and those who do not. Reliable scale: The academic self-efficacy scale used in the study demonstrates high reliability, with a Cronbach's Alpha coefficient of 0.890. Implications for practice: The findings suggest that tutoring may not be the sole determinant of academic self-efficacy in upper grade students, prompting educators and parents to consider alternative strategies to enhance students' belief in their abilities. Keyword: Academic Self-Efficacy, Tutoring, Upper Grade Students, Quantitative Comparison, Elementary School